On 4-5 October 2012 was held scientific-practical conference " - T, T (Pathologia, 2013)
Urgent issues of pathological morphology», dedicated to the 90th anniversary of Department of Pathologic and Topographic Anatomy of SHUPYK NATIONAL MEDICAL ACADEMY OF POSTGRADUATE EDUCATION The Department of Pathologic and Topographic Anatomy was established in 1990. Till 1990 there were two different departments. The Department of Pathologic Anatomy was founded in 1922. It is based in the pathologoanatomic Department of the Kyiv Regional Clinical Hospital. During the period of the existence of the Department of Pathologic Anatomy, over 40 dissertations in the speciality “Pathologic anatomy” were defended under the supervision of the teaching staff members, 5 monographs and more than 500 scientific works were published. The department is a scientific-methodological centre in Ukraine in specialities “Pathologic Anatomy” and “Pediatric Pathologic Anatomy”. Curricula and Syllabi on all types of specialization, internships, pre-certification, topical advanced training courses on pathologic anatomy, pediatric pathologic anatomy were created. In 2000, a testing certification program ААS-2000 for doctors-pathologoanatomists and pediatric pathologoanatomists was reviewed and approved by the Min. The department of Topographic anatomy was founded in 1945. Its premises are located in the central building of P.I.Shupyk KMAPHE. The department carries out diagnostic and consultative work at base departments (the Kyiv Regional Clinical Hospital No. 1, the Kyiv City hospital No. 9, the Regional Oncological Dispensary), as well as other medical establishments of Kyiv, medical institutions and pathologoanatomic offices of Ukraine.